Teacher Education for Sustainable Development: A Review of an Emerging Research Field - Fischer, Daniel; King, Jordan; Rieckmann, Marco; Barth, Matthias; Büssing, Alexander; Hemmer, Ingrid; Lindau-Bank, Detlev (Journal of teacher education)
Teacher Education for Sustainable Development (TESD) is a niche innovation in teacher education that empowers teachers to prepare learners to address global socio-environmental challenges. To advance the diffusion of this niche innovation into general teacher education, this article offers a systematic literature review based on a qualitative analysis of 158 peer-reviewed publications on TESD research. Our results show that TESD research is a growing field characterized by five types of inquiry: designing learning environments, understanding learner attributes, measuring learning outcomes, promoting systems change, and advancing visions for the field. Major innovation potentials of TESD for more general teacher education are its emphasis on the grand socio-environmental challenges of our times, methodologies to engage with knowledge diversity (e.g., inter/transdisciplinarity), and sustainability science learning approaches (e.g., backcasting). We suggest that future work builds from this review to strengthen links between teacher education and TESD in enhancing quality education.